Sindrom Chorea Hiperglikemia Ganglia Basalis: Laporan Kasus - Puspita, Amelia; Sumada, I Ketut; Wiratni, Ni Ketut Candra; Yuliani, Desie; Jayanthi, Ni Made Kurnia Dwi (Cermin Dunia Kedokteran, 2024)
Background: Chorea hyperglycemia basal ganglia (C-H-BG) syndrome is an uncommon manifestation of diabetes mellitus seen in patients with poor glycemic control. Case: A 74-year-old poorly controlled diabetic women with acute onset of movement disorder in the form of uncontrolled choreiform movements of her left upper and lower extremity. Her initial glucose level was 289 mg/dL and HbA1C was 9.5%. Discussion: Most C-H-BG patients are older Asian female. Female predisposition is probably related to the estrogen decline during menopause, resulting in gamma-aminobutyric acid (GABA) depletion or dopamine receptors hypersensitivity and enhancement of dopaminergic system. Its pathophysiology has not been entirely defined. Conclusion: C-H-BG is a rare manifestation of poorly controlled diabetes. Early recognition and treatment of elevated blood glucose levels appear to lead to total resolution.